2017
DOI: 10.1161/jaha.117.005506
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Mechanistic Target of Rapamycin Complex 1 (m TORC1) Inhibition by Rapamycin Treatment of Pregnant Mice Causes Intrauterine Growth Restriction and Alters Postnatal Cardiac Growth, Morphology, and Function

Abstract: BackgroundFetal growth impacts cardiovascular health throughout postnatal life in humans. Various animal models of intrauterine growth restriction exhibit reduced heart size at birth, which negatively influences cardiac function in adulthood. The mechanistic target of rapamycin complex 1 (mTORC1) integrates nutrient and growth factor availability with cell growth, thereby regulating organ size. This study aimed at elucidating a possible involvement of mTORC1 in intrauterine growth restriction and prenatal hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…mTOR acts as a positive regulator of system A, system L, and taurine placental amino acid transporter activity, all of which are necessary for amino acid transport to the fetus and thus fetal growth. Its role in human fetal growth is not well established, but intrauterine growth restriction has been described in mouse models . mTOR inhibitors are generally well tolerated in young children especially if long‐term treatment is not needed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mTOR acts as a positive regulator of system A, system L, and taurine placental amino acid transporter activity, all of which are necessary for amino acid transport to the fetus and thus fetal growth. Its role in human fetal growth is not well established, but intrauterine growth restriction has been described in mouse models . mTOR inhibitors are generally well tolerated in young children especially if long‐term treatment is not needed .…”
Section: Discussionmentioning
confidence: 99%
“…33 Its role in human fetal growth is not well established, but intrauterine growth restriction has been described in mouse models. 34 mTOR inhibitors are generally well tolerated in young children especially if long-term treatment is not needed. 35 One study of 18 children specifically evaluated the growth of children on everolimus until age 3, and except for in one child, there was no negative impact of everolimus on growth rate.…”
Section: Growth Restrictionmentioning
confidence: 99%
“…mTORC1 activates p70S6 kinase followed by phosphorylation of ribosomal protein S6 whereas mTORC2 activates Akt by phosphorylation at Ser473. Rapamycin, as a commonly used inhibitor of mTOR, was found preferentially inhibits mTORC1 [41], although recent studies indicate that long-term treatment of rapamycin also inhibits mTORC2 [42]. Previous studies suggested that mTORC1 is the dominant complex stimulated by IR injury [43].…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have demonstrated that rapamycin treatment in pregnant mice inhibits cardiac function, growth and mass by mTOR inhibition in heart development [49]. Therefore, we treated neonatal mice with rapamycin in late gestation (starting at 15.5 dpc) to determine the effect of prenatal mTOR inhibition on salivary gland development using rapamycin injection methods developed previously [49,50]. Therefore, we treated neonatal mice with rapamycin in late gestation (starting at 15.5 dpc) to determine the effect of prenatal mTOR inhibition on salivary gland development using rapamycin injection methods developed previously [49,50].…”
Section: Mtor Inhibition By Rapamycin Affects Salivary Gland Developmmentioning
confidence: 99%
“…Mammalian target of rapamycin plays a critical role in growth control and development [2,32,48]. Recent investigations have demonstrated that rapamycin treatment in pregnant mice inhibits cardiac function, growth and mass by mTOR inhibition in heart development [49]. However, it has not been evaluated whether mTOR inhibition by rapamycin injection affects salivary gland development.…”
Section: Mtor Inhibition By Rapamycin Affects Salivary Gland Developmmentioning
confidence: 99%